Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Pemecahan Masalah Peserta Didik Kelas XI MIA di SMAN 11 Makassar (Studi Materi Pokok Laju Reaksi) - Palajukan, Yulianti; Sugiarti, Sugiarti; Herawati, Netti (ChemEdu, 2021)
This study is a quasi-experimental research (Quasi Experiment) that aims to determine the effect of guided inquiry learning model to the problem-solving ability of students Class XI SMAN 11 Makassar. The study design used was "posttest-Only Control Group Design ".The study population was the students of class XI MIA SMA Negeri 11 Makassar consisting of six classes, while the sample is a class XI MIA 4 as an experimental class and class XI MIA 6 as the control class with the number of students each 34 people. The experimental class was studied by guided inquiry model. While the control class was with conventional learning models.The independent variable in this study was guided inquirí learning model and conventional learning model. The dependent variable is the ability to solving problem.Data retrieval problem solving skills performed by administering the test problem solving abilities. Problem-solving abilities data were analyzed using descriptive statistics and inferential statistics. The results of inferential statistical analysis of the data prerequisite troubleshooting capabilities indicate that the data on the class experimental and control classes were not normally distributed, but had a homogeneous variance. Hypothesis testing was done by using a non-parametric test of Mann-Whitney test with α = 0.05 was obtained Zcalculated> Ztable (2:02> 1.64). The effect of guided inquiry learning model to the problem-solving ability of students in class XI MIA SMAN 11 Makassar studies on the subject matter of the reaction rate.